YIIFSWA II OPENDAY - Exhibition - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
Yam products display at YIIFSWA-II Open Day. YIIFSWA-II showcases High Ratio Propagation Technologies and demonstrates large scale production of early generation seed yam at the project's open day in 2018.